2011
DOI: 10.1111/j.1654-109x.2010.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Clear-felling effects on colonization rates of shade-tolerant forest herbs into a post-agricultural forest adjacent to ancient forest

Abstract: Question: Does clear‐felling influence forest herb colonization into post‐agricultural forest? Location: A stand of poplar cultivars with a dense understorey of Acer pseudoplatanus in Muizen forest (northern Belgium), planted in 1952 on farmland adjacent to ancient forest and clear‐felled in 1997. Methods: Shade‐tolerant forest herbs were surveyed in 112 grid‐based sample plots: just before clear‐felling, and 5 and 10 yr afterwards. Shade‐tolerant herbs were subdivided into ancient forest species (AFS) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…Studies on recruitment of ancient forest species in post-agricultural forests have revealed effects of soil characteristics and light availability (e.g. Baeten et al 2009b;Brunet et al 2000;De Keersmaeker et al 2010;Graae et al 2004;Honnay et al 1999a;Koerner et al 1997). Tree species effects on recruitment of ancient forest species in post-agricultural forests have, however, never been studied in detail (but see Dzwonko and Loster 1997;Wulf and Heinken 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Studies on recruitment of ancient forest species in post-agricultural forests have revealed effects of soil characteristics and light availability (e.g. Baeten et al 2009b;Brunet et al 2000;De Keersmaeker et al 2010;Graae et al 2004;Honnay et al 1999a;Koerner et al 1997). Tree species effects on recruitment of ancient forest species in post-agricultural forests have, however, never been studied in detail (but see Dzwonko and Loster 1997;Wulf and Heinken 2008).…”
Section: Introductionmentioning
confidence: 97%
“…We conclude that even though park management optimizes tree and shrub density for visitors, the average shade and intermediate disturbances seem to improve the overall environment in a stand toward an optimum condition for all shade-tolerant species (Von Oheimb and Härdtle 2009; De Keersmaeker et al. 2011; Liira and Paal 2013). However, some management treatments, such as intensive early summer mowing supported only corridor specialists, probably because corridor specialists with hemirosette growth form have higher mowing tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Even without a dimension of time, the PNV concept is valuable as a null model (Somodi et al 2012), but an integration of the AFS concept into the PNV concept can also facilitate the use of PNV maps for restoration purposes. The time for forest vegetation to develop to PNV is determined by colonization by AFS and colonization rates of AFS can be quantified (e.g., see Brunet and von Oheimb 1998;Bossuyt et al 1999;De Keersmaeker et al 2011). An analysis of landscape factors and environmental quality that influence the colonization rate by AFS enables the comparison of the potentials of sites that are considered for restoration.…”
Section: Application Of Pnv Maps For Forest Restoration Projectsmentioning
confidence: 99%